Development Of Traditional Para Fruit Game-Based Learning Media For Integer Counting Material At Sdn Selat Gelam District - Bambang Herianto; Tety Kurmalasari; Zaitun; Abdul Malik; Encik Abdulhajar (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
The rapid development of the 21st century requires teachers to be creative in integrating local culture into the classroom, especially in abstract subjects like mathematics. This study aims to develop learning media based on the traditional game of